The Influence of the Snake and Ladder Game on the Learning Outcomes of Hadith among Third-Grade Students - Nur Hidayatul Lailiyah (Jurnal Penelitian Pendidikan, 2025)
The low learning outcomes of third-grade Madrasah Ibtidaiyah students in hadith are due to the learning process, which is still dominated by conventional methods, causing students to easily become bored and less active. This study aims to determine the effect of using snake and ladder learning media on the learning outcomes of third-grade students at MIN 1 Surabaya. This study is a quantitative study with a quasi-experimental design using a pretest-posttest control group design. The research sample consisted of two classes, namely class III-A as the experimental class and class III-B as the control class, each with 23 students. The data collection technique used learning outcome tests in the form of pre-tests and post-tests, while data analysis was performed using the Mann Whitney U nonparametric statistical test. The results showed that the average learning outcomes of students in the experimental class were higher than those in the control class, namely 77.23 in the experimental class and 54.26 in the control class. The Mann Whitney U test results showed a significance value of 0.000 < 0.05, which means that there was a significant effect of using the snake and ladder media on students' learning outcomes in hadith. The snake and ladder media proved to be able to increase student activity, enthusiasm, and understanding in hadith learning. Therefore, the snake and ladder media is recommended as an effective alternative learning media to improve hadith learning outcomes in Madrasah Ibtidaiyah.